Efficacy of Virtual Reality and Exergaming in Improving Balance in Patients With Multiple Sclerosis: A Systematic Review and Meta-Analysis - Calafiore, Dario; Invernizzi, Marco; Ammendolia, Antonio; Marotta, Nicola; Fortunato, Francesco; Paolucci, Teresa; Ferraro, Francesco; Curci, Claudio; Cwirlej-Sozanska, Agnieszka; de Sire, Alessandro (Frontiers in Neurology, 2021)
Multiple sclerosis (MS) is one of the most common causes of neurological progressive disease and can lead to loss of mobility, walk impairment, and balance disturbance. Among several rehabilitative approaches proposed, exergaming and virtual reality (VR) have been studied in the recent years. Active video game therapy could reduce the boredom of the rehabilitation process, increasing patient motivation, providing direct feedback, and enabling dual-task training. Aim of this systematic review was to assess the efficacy of exergaming and VR for balance recovery in patients with MS. PubMed, Scopus, and Web of Science were systematically searched from the inception until May 14, 2021 to identify randomized controlled trials (RCTs) presenting: patients with MS as participants, exergaming and VR as intervention, conventional rehabilitation as comparator, and balance assessment [Berg Balance Scale (BBS)] as outcome measure. We also performed a meta-analysis of the mean difference in the BBS via the random-effects method. Out of 93 records, this systematic review included and analyzed 7 RCTs, involving a total of 209 patients affected by MS, of which 97 patients performed exergaming or VR and 112 patients underwent conventional rehabilitation. The meta-analysis reported a significant overall ES of 4.25 (p < 0.0001), showing in the subgroup analysis a non-significant ES of 1.85 (p = 0.39) for the VR and a significant ES of 4.49 (p < 0.0001) for the exergames in terms of the BBS improvement. Taken together, these findings suggested that balance rehabilitation using exergames appears to be more effective than conventional rehabilitation in patients affected by MS.